Coordination of bis(pyrazol-1-yl)amine to palladium(II): influence of the co-ligands and counter-ions on the molecular and crystal structures - María de los Angeles Mendoza; Sylvain Bernès; Guillermo Mendoza-Díaz (Acta Crystallographica Section E: Crystallographic Communications, 2015)
The structures of a series of complexes with general formula n[Pd(pza)X]Y·mH2O (n = 1, 2; X = Cl, Br, I, N3, NCS; Y = NO3, I, N3, [Pd(SCN)4]; m = 0, 0.5, 1) have been determined, where pza is the tridentate ligand bis[2-(3,5-dimethylpyrazol-1-yl)ethyl]amine, C14H23N5. In all complexes, {bis[2-(3,5-dimethylpyrazol-1-yl-κN2)ethyl]amine-κN}chloridopalladium nitrate, [Pd(pza)Cl]NO3, (1), {bis[2-(3,5-dimethylpyrazol-1-yl-κN2)ethyl]amine-κN}bromidopalladium nitrate, [Pd(pza)Br]NO3, (2), {bis[2-(3,5-dimethylpyrazol-1-yl-κN2)ethyl]amine-κN}iodidopalladium iodide hemihydrate, [Pd(pza)I]I·0.5H2O, (3), azido{bis[2-(3,5-dimethylpyrazol-1-yl-κN2)ethyl]amine-κN}palladium azide monohydrate, [Pd(pza)N3]N3·H2O, (4), and bis[{bis[2-(3,5-dimethylpyrazol-1-yl-κN2)ethyl]amine-κN}(thiocyanato-κN)palladium] tetrakis(thiocyanato-κS)palladate, [Pd(pza)NCS]2[Pd(SCN)4], (5), the [Pd(pza)X]+ complex cation displays a square-planar coordination geometry, and the pza ligand is twisted, approximating twofold rotation symmetry. Although the pza ligand is found with the same conformation along the series, the dihedral angle between pyrazole rings depends on the co-ligand X. This angle span the range 79.0 (3)–88.6 (1)° for the studied complexes. In (3), two complex cations, two I− anions and one water molecule of crystallization are present in the asymmetric unit. In (5), the central amine group of pza is disordered over two positions [occupancy ratio 0.770 (18):0.230 (18)]. The complex [Pd(SCN)4]2− anion of this compound exhibits inversion symmetry and shows the Pd2+ transition metal cation likewise in a square-planar coordination environment. Compound (5) is also a rare occurrence of a non-polymeric compound in which the pseudohalide ligand NCS− behaves both as thiocyanate and isothiocyanate, i.e. is coordinating either through the N atom (in the cation) or the S atom (in the anion).